Pengendalian Kualitas Produksi Keripik Pisang pada UMKM Pekopen Menggunakan Peta Kendali NP dan Kapabilitas Proses - Setiawan, Handika; Herwanto, Dene; Nugraha, Billy (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Pekopen MSMEs produce banana chips that always strive to produce good products, but in fact they still find some products produced are not in accordance with standards. These problems can be solved using nP control maps, Ishikawa diagrams, and process capabilities, as well as calculations using minitab software. By using some of these methods, it is expected to find the factors that cause product defects. There are several variables to assess the defects of banana chip products, including shape, color, and size variables. The results of this study show the factors that cause defects in banana chip products, namely method factors caused by the manual banana chip cutting process, inaccurate selection of raw materials, manual frying process, and manual packaging process. In addition, it was found that the level of specifications and standards for process capabilities was not less than 95% and no more than 3% of the inability of MSMEs to produce banana chips in accordance with specifications and standards.